Makna Kompensasi Dalam Perspektif Keberlangsungan Hidup (Studi Kasus Motivasi dan Kompensasi Satuan Pekerja Keamanan Outsourcing pada PT Pesonna Optima Jasa Di Sleman Yogyakarta) - Kundarti, Fitria Kundarti; Rini, Ika Tirta Candra; Setiawati, Trias Setiawati (Program Studi Manajemen, 2022)
The development of the world of work is growing so rapidly with the outsourcing work system. The outsourcing system is a work system that uses the services of a power expert in managing a particular job or project. There are some negative perceptions from the public about the status of outsourced employees because they are considered to have lower compensation rights and there is no guarantee of career certainty and employment status in the long term. In addition, the number of complaints and dissatisfaction with receiving compensation for outsourcing employees, directly or indirectly can affect work motivation. This study focuses on the motivation and compensation of the Outsourcing Security Worker Unit at PT Pesonna Optima Jasa in Sleman Yogyakarta entitled